Dynamics expression of Osr40c1 gene and growth of maize (Zea mays) calluses in responding to salt stress - TRIONO BAGUS SAPUTRO; NUR FADLILLATUS SHOLIHAH; DINI ERMAVITALINI (Biodiversitas Journal of Biological Diversity, 2017)
Saputro TB, Sholihah NF, Ermavitalini D. 2017. Dynamics expression of Osr40c1 gene and growth of maize (Zea mays) calluses in responding to salt stress. Biodiversitas 18: 801-808. Maize (Zea mays L) is one of the most planted cereal plants worldwide. The demand of maize plant is increased over the years since its various usage in industry. Unfortunately, the production rate does not meet the demands caused by the significant reduction of plantation area for housing and the others building. The marginal saline soil area can be a promising area to grow the maize although contains a high amount of salt. The high concentration of salt can significantly reduce the plant growth and productivity. The aims of this study were to determine the tolerant level of Manding and Bluto varieties against salt stress. There were two main stages on this research. First, callus induction through in vitro culture (MS0 + 2,4-D 3 mg/L), then the calluses were subcultured on the selection medium (MS0 + 2,4-D 3 mg/L + NaCl concentrations (0, 2500, 5000 and 7500 mg/L)). Second, Q-PCR analysis was used to observe the differences of gene expression level. The result shows that NaCl stress can alter the color of callus, from yellow to brown. The percentage of surviving callus was 100% in both varieties, although the callus weight decreased along with the increment of NaCl concentrations. In 7500 mg/L, Manding has 0.023 g in fresh weight, while Bluto 0,027 gr. Interestingly, the expression of Osr40c1 gene showed different level between those two varieties. Manding had only 0.82 fold, while Bluto had 4.86 folds compared with the control. Taken together, Bluto has a better performance in high content of NaCl.